2013
DOI: 10.1177/1473225413492055
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Factors Affecting Children in Legal Contexts

Abstract: Developmental factors affect the way that children and young people behave in legal contexts. We first discuss developmental factors such as cognitive and emotional development, social expectations and suggestibility that affect young victims and suspects. We then describe some implications of these developmental factors for police interviewers and for the youth justice system more generally and call for the more differentiated treatment of young people according to their age and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…It would, therefore, appear that short periods between the time of abuse and the child's disclosure will be a rarity (Priebea & Svedin, 2008). With this in mind, it is crucial that researchers and practitioners recognize that various situational and developmental factorscognitive, emotional and socialcan compromise the effective participation of young people in legal contexts (Bruck, Ceci, & Principe, 2006;Lamb & Sim, 2013). Regardless of such realities, lawyers will seek to present disclosure evidence to their best advantage in the courtroom.…”
Section: Abuse Type and Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…It would, therefore, appear that short periods between the time of abuse and the child's disclosure will be a rarity (Priebea & Svedin, 2008). With this in mind, it is crucial that researchers and practitioners recognize that various situational and developmental factorscognitive, emotional and socialcan compromise the effective participation of young people in legal contexts (Bruck, Ceci, & Principe, 2006;Lamb & Sim, 2013). Regardless of such realities, lawyers will seek to present disclosure evidence to their best advantage in the courtroom.…”
Section: Abuse Type and Severitymentioning
confidence: 99%
“…Some of this have been covered by the considerable literature concerning developmental factors that also affect child victims within legal and forensic contexts (e.g. Lamb & Sim, 2013), and which includes memory, communicative skills, social orientation, cognitive development and peer influence in depth. The approach of this article thus has the capability to be taken forward through the analysis of the aforementioned additional factors.…”
Section: Limitationsmentioning
confidence: 99%
“…There are important factors to assess when preschool children are interviewed in investigative interviews, including their language development, memory capacity, vulnerability to suggestibility and psychosocial aspects (Bruck et al 2006, Lamb andSim 2013). Research has shown that interviewers often fail to ask age-appropriate and understandable questions to children and that this may lead to incomplete information from them (Saywitz et al 1990(Saywitz et al , 1993.…”
Section: Challenges Encountered When Interviewing Preschool Childrenmentioning
confidence: 99%
“…Thus, while young people may have the ability to discern right from wrong at a young age, they have a limited ability ‘both to appreciate the risks of doing certain things and to appreciate the significance of the resulting harm’ (Gross, 1979, p. 151). They are less able to see things in long-term perspective, look at things from other viewpoints, and less able to control impulses (Sentencing Advisory Council of Victoria, 2012, referring particularly to research of Scott and Steinberg, 2008; see also Blustein, 1985; Cauffman & Steinberg, 2000; Fried & Reppucci, 2001; Steinberg & Scott, 2003; Johnson, Blum, & Giedd, 2009; Monahan, Steinberg, & Cauffman, 2009; Lamb & Sim, 2013; Pillay, 2015). This process of developing the capacities necessary for criminal responsibility does not take place at a consistent pace and there can be vast differences between individuals of the same biological age (see, for instance, Cauffman & Steinberg, 2000).…”
Section: Is There a Need To Retain The Rebuttable Presumption Of Dolimentioning
confidence: 99%
“…Such expert opinion is one piece of evidence to be assessed by the fact finder in the context of all other evidence that might be available. Whether a child had criminal capacity at the time of the offence is dependent on many varied factors (see, for example, Lam and Sim, 2013; Skelton, 2013). Requiring expert evidence in every case carries the danger of medicalising and pathologising the issue and making it appear that the judge, magistrate, or jury are routinely not in a position to assess the available evidence and always lack relevant experience.…”
Section: Issues With the Rebuttable Presumption Of Doli Incapaxmentioning
confidence: 99%